2018
DOI: 10.1111/desc.12757
|View full text |Cite
|
Sign up to set email alerts
|

Natural reference: A phylo‐ and ontogenetic perspective on the comprehension of iconic gestures and vocalizations

Abstract: The recognition of iconic correspondence between signal and referent has been argued to bootstrap the acquisition and emergence of language. Here, we study the ontogeny, and to some extent the phylogeny, of the ability to spontaneously relate iconic signals, gestures, and/or vocalizations, to previous experience. Children at 18, 24, and 36 months of age (N = 216) and great apes (N = 13) interacted with two apparatuses, each comprising a distinct action and sound. Subsequently, an experimenter mimicked either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 56 publications
(84 reference statements)
1
28
1
Order By: Relevance
“…In principle, this definition would include numerous cases of described intention movements and gesture types where form resembles function, such as a beckoning gesture in sexual initiations (Genty & Zuberbühler, ), a ‘hip shimmy’ (involving rapid lateral hip movements) resulting in genito‐genital rubbing (Douglas & Moscovice, ), or an outstretched leg of a mother persuading her infant to climb on her for joint travel (Fröhlich, Wittig & Pika, ). Although experimental studies reveal that great apes have difficulties with spontaneously comprehending iconic signals, it was also shown that they learn them faster than arbitrary gestures (Bohn, Call & Tomasello, ; Bohn et al ., ). In conclusion, the presence of iconicity is more established and striking in the motor‐visual domain, and has not been shown in the vocal‐auditory domain of non‐human species.…”
Section: Cognitive Mechanisms Identified In Non‐human Gestures and Vomentioning
confidence: 97%
See 1 more Smart Citation
“…In principle, this definition would include numerous cases of described intention movements and gesture types where form resembles function, such as a beckoning gesture in sexual initiations (Genty & Zuberbühler, ), a ‘hip shimmy’ (involving rapid lateral hip movements) resulting in genito‐genital rubbing (Douglas & Moscovice, ), or an outstretched leg of a mother persuading her infant to climb on her for joint travel (Fröhlich, Wittig & Pika, ). Although experimental studies reveal that great apes have difficulties with spontaneously comprehending iconic signals, it was also shown that they learn them faster than arbitrary gestures (Bohn, Call & Tomasello, ; Bohn et al ., ). In conclusion, the presence of iconicity is more established and striking in the motor‐visual domain, and has not been shown in the vocal‐auditory domain of non‐human species.…”
Section: Cognitive Mechanisms Identified In Non‐human Gestures and Vomentioning
confidence: 97%
“…faster) than non‐linguistic vocal communication in creating signalling systems from scratch, and both studies showed that combining gestures and vocalizations did not improve performance beyond gestures alone. In an experimental study on children, iconic gestures were understood better than iconic vocalizations by 24‐ and 36‐month‐olds (but not 18‐months‐olds), suggesting that iconic gestures support language ontogeny (Bohn, Call & Tomasello, ). In fact, iconic signals appear to emerge with the instantiation of most human communication systems: many signals of American Sign Language, in which gestures and facial expressions carry the full communicative burden (Goldin‐Meadow, ), arose as iconic representations of objects or actions before gradually losing the original resemblance between form and referent (Frishberg, ).…”
Section: Cognitive Mechanisms Identified In Non‐human Gestures and Vomentioning
confidence: 99%
“…Nicaraguan sign language; Kegl et al, 1999;Senghas & Coppola, 2001; see also Bohn, Kachel, & Tomasello, 2019). Recent work has suggested that reference may be easier to establish in gesture than vocalization (Fay et al, 2014), prompting others to theorize that human conventional communication may have originated in gesture (Bohn, Call, & Tomasello, 2019).…”
Section: Parallels Between Gesture and Languagementioning
confidence: 99%
“…For children, unlike adults, there may be a dissociation such that children more flexibly change their spoken utterances in response to the communicative requirements than their gestures --perhaps due to a greater amount of experience and practice with conventional communication. Alternatively, recent findings and theories regarding the primacy of gesture over spoken language (Bohn, Call, & Tomasello, 2019;Fay et al, 2014) motivate the contrasting prediction that children may actually be more successful in tailoring their gestural communication for their listeners' needs than their spoken conventional communication.…”
Section: The Development Of Gestural Communicationmentioning
confidence: 99%
“…[49]). Bohn et al [50] found that 24-month-olds could understand multimodal iconic signals, but not signals that were unimodal (vocal or gestural). Evidence of how the vocal and gestural modality are combined in language also stems from experimental research on adults, where research has shown that vocal and gestural signals are integrated at behavioural, cognitive and neural levels (e.g.…”
Section: Modern Human Communicative Behaviourmentioning
confidence: 99%